PENGUATAN MODAL SOSIAL DALAM PENANGANAN PRODUK OLAHAN KOPI PADA KOMUNITAS PETANI KOPI DI KABUPATEN JEMBER - Rokhani Said (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2012)
Study of social capital in coffee farmer community to diversify product has not been done. This study aimed: (1) to describe the conditions of social capital in farmer community who diversify coffee products, (2) to map the components of social capital which are still strong and which still need strengthening, (3) to formulate development strategies of product diversification on coffee products. The location of study is determined purposively in 5 (five) village in five sub districts in Jember District: Sidomulyo in Silo Sub District, Sucopangepok in Jelbuk Sub District, Rowosari in Sumberjambe Sub District, Sumbersalak in Ledokombo Sub District and Kemiri in Panti Sub District. The data were analyzed using descriptive method. The results of this study are: the strong element of social capital are: partnership, trust, norm, custom and local culture value, tolerance, local wisdom and knowledge, social leadership, community participation, independence, freedom of mobility , the ability to buy "small" and "large" commodity, household decisions, relative freedom and domination of family also economic security and contribution to family. The elements of social capital that is still weak and should be strengthened are: transaction network (sale), product processing for diversification, packaging, togetherness and involvement in a campaign or protest. Strategy to develop product diversification of coffee based on social capital are: (1) lending with approriate scheme to coffee harvest time, (2) utilizing strong social capital in diversification product of coffee as well as strengthening elements of social capital that is still weak, (3) increasing capacity of coffee farmers through training to improve skill and self-reliance in coffee processing, (4) providing machinery to apply wet coffee processing, (5) establishing program for capacity development of coffee farmers in processing, (6) strengthening farmer institutions, (7) expanding marketing network, (8) strengthening institution of cooperation to improve bargaining position of farmers (9) sustainable guidance and assistance in application of innovative technology (10) determinating regions as coffee centres by utilizing strong elements of social capital within community. Key words: social capital, community, coffee farmer.